Memutus Rantai Statelessness: Mengatasi Tantangan Hak Asasi Manusia yang Dihadapi Suku Pegunungan di Thailand - Mirea Artesani (Jurnal HAM, 2025)
This paper examines the issue of statelessness and its impact on the hill tribes of northern Thailand, a mix of ethnic groups populating the Thai, Myanmar, and Laos borderlands who are facing significant challenges in accessing basic human rights due to their lack of Thai citizenship. The paper explores the historical context of how the hill tribes came to be stateless, as well as the various obstacles they encounter in obtaining legal recognition as citizens of Thailand. Drawing on academic literature and Thai legislation, this paper argues that the denial of citizenship represents a fundamental violation of human rights. It also emphasizes the secondary rights violations due to various levels of discrimination and marginalization that these groups experience, such as restricted access to education, healthcare, and job possibilities. Finally, the paper considers potential policy solutions that could address the issue of statelessness among the hill tribes. These solutions include reforming citizenship laws to provide greater access to citizenship, as well as implementing programs to promote the inclusion of hill tribe communities in Thai society while also preserving their cultural heritage. Ultimately, the paper argues that addressing the issue of statelessness among the hill tribes is not only a matter of human rights, but also essential for building a more inclusive and equitable society.